Pharmacologic Approaches for the Management of Apathy in Neurodegenerative Disorders - Bogdan, Anamaria; Manera, Valeria; Koenig, Alexandra; David, Renaud (Frontiers in Pharmacology, 2020)
Apathy is one of the most frequent behavioural disturbances in many neurodegenerative disorders and is known to have a negative impact on the disease progression, particularly in Alzheimer’s disease. Therapeutic options are currently limited and non-pharmacological approaches should constitute first line treatments. Pharmacological agents likely to reduce apathy levels are lacking. The objective of the present article is to review recent pharmacological treatments for apathy in neurodegenerative disorders. The Pubmed database was searched with a particular focus on articles published as of January 2017. Current main levels of evidence have been reported so far with cholinergic, glutamatergic and dopaminergic agents to reduce levels of apathy, despite several conflicting results. Treatment duration and samples sizes may have however decreased the validity of previous results. Ongoing studies involving more participants/treatment duration or distinct neural pathways may provide new insights in the treatment of apathy in neurodegenerative disorders.